STUDY OF THE OUTPUT VOLTAGE SPECTRUM OF A CONTACTLESS AC GENERATOR ON A VIRTUAL MODEL - ZENOVYCH, OLEKSANDR; BURCHYN, YURIY; VASYLENKO, ROMAN; HEORGIEV, YURIY; PAYANOK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
At present, the control of the aircraft power supply system is carried out by the voltage level in the on-board network at a given load. When conducting in-depth control, for example, using automated control systems, the parameters of transient and steady processes (overshoot, regulation time, static error, etc.) are measured and evaluated using a parameter analyzer on the principle of "suitable - unsuitable", and the analysis results are issued in the automated control system in the form of generalized information about the state of the generation channel. The disadvantage of the considered control method is the need to use additional devices in each controlled unit, which in some cases are not inferior in complexity to the control object. Therefore, the most rational solution to the problems of automatic control of the state of the power supply system in the complex of all aircraft equipment is the use of on-board automated control systems based on digital computers. Such automated control systems should provide continuous monitoring of operability in flight, and during operational types of aircraft preparation for flights and after flight - monitoring with fault finding up to the variable block. When using microprocessor computing devices in promising power supply systems, which are assigned the functions of regulation, protection, control and control, along with diagnostics, the task of predicting the technical condition of the system can be solved, which will allow moving to a more progressive method of operation, namely operation by condition. That is why the paper presents the results of research on a synchronous generator as an object of diagnostics on a virtual model built in the MatLab/Simulink simulation environment taking into account the design features of cascade synchronous generators of the GT series: the presence of three generators in the machine - a magnetoelectric exciter, an electromagnetic exciter, an electromagnetic main generator; an uncontrolled three-phase rotating rectifier; a phase-pulse voltage regulator with a controlled rectifier. The conducted studies of the generator operation made it possible to obtain the spectra of the generator output voltage in different modes in good condition and in the event of typical failures of the electronic part of the generator. The obtained modeling results show the principle possibility of identifying typical failures by the spectra of the generator output voltage. When diagnosing the generator, it is advisable to also monitor the spectral composition of the output voltage of the voltage regulator, which will allow a more reliable assessment of the state of the electric machine. At the same time, it is important to take into account the influence of the generator operating mode on the spectra of the generator output voltage and voltage regulator. The results of the research can be useful in creating ground and onboard automated control systems for power supply systems on microprocessor computing devices.